Strategies to improve the stability of amorphous solid dispersions in view of the hot melt extrusion (HME) method - AL-japairai, Khater Ahmed Saeed; Almurisi, Samah Hamed; Syed, Mahmood; Madheswaran, Thiagarajan; Chatterjee, Bappaditya; Sri, Prasanthi; Nadiatul Azra, Ahmad Mazlan; Al Hagbani, Turki; Alheibshy, Fawaz (Elsevier B.V., 2023)
Oral administration of drugs is preferred over other routes for several reasons: it is non-invasive, easy to administer, and easy to store. However, drug formulation for oral administration is often hindered by the drug's poor solubility, which limits its bioavailability and reduces its commercial value. As a solution, amorphous solid dispersion (ASD) was introduced as a drug formulation method that improves drug solubility by changing the molecular structure of the drugs from crystalline to amorphous. The hot melt extrusion (HME) method is emerging in the pharmaceutical industry as an alternative to manufacture ASD. However, despite solving solubility issues, ASD also exposes the drug to a high risk of crystallisation, either during processing or storage. Formulating a successful oral administration drug using ASD requires optimisation of the formulation, polymers, and HME manufacturing processes applied. This review presents some important considerations in ASD formulation, including strategies to improve the stability of the final product using HME to allow more new drugs to be formulated using this method.